2010
DOI: 10.1152/ajpregu.00163.2010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of PGHS-2 and glutamatergic mechanisms controlling the ovine fetal hypothalamus-pituitary-adrenal axis

Abstract: Prostaglandins, generated within the fetal brain, are integral components of the mechanism controlling the fetal hypothalamus-pituitary-adrenal (HPA) axis. Previous studies in this laboratory demonstrated that prostaglandin G/H synthase isozyme 2 (PGHS-2) inhibition reduces the fetal HPA axis response to cerebral hypoperfusion, blocks the preparturient rise in fetal plasma ACTH concentration, and delays parturition. We also discovered that blockade of N-methyl-d-aspartate (NMDA) receptors reduces the fetal ACT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Res also inhibited NMDA-induced neuronal death, intracellular calcium increase and reactive oxygen species generation in rat cortical neurons, confirming the neuroprotective effect of Res [11,28]. However, other studies have shown that pretreatment with Res did not alter the magnitude of the hypothalamus-pituitary-adrenal axis response to NMDA [29]. Furthermore, some studies have shown that treating neurons with Res did not protect them from Glu/NMDA-induced depletion of nicotinamide adenine dinucleotide (NAD+), an important energy substrate and cofactor in multiple metabolic reactions, and death [30].…”
Section: Res-mediated Neuroprotective Effects Against Glu-induced Excsupporting
confidence: 55%
“…Res also inhibited NMDA-induced neuronal death, intracellular calcium increase and reactive oxygen species generation in rat cortical neurons, confirming the neuroprotective effect of Res [11,28]. However, other studies have shown that pretreatment with Res did not alter the magnitude of the hypothalamus-pituitary-adrenal axis response to NMDA [29]. Furthermore, some studies have shown that treating neurons with Res did not protect them from Glu/NMDA-induced depletion of nicotinamide adenine dinucleotide (NAD+), an important energy substrate and cofactor in multiple metabolic reactions, and death [30].…”
Section: Res-mediated Neuroprotective Effects Against Glu-induced Excsupporting
confidence: 55%
“…We know, from previous results in this laboratory, that NMDA stimulates fetal ACTH secretion [20]. However, it is also known that the fetal ACTH response to hypoxia is dependent on the carotid chemoreflex [10, 21, 22], and that at least one report in the literature suggests that ketamine modulates fetal ovine cardiovascular responses to chemoreceptor stimulation [16].…”
Section: Discussionmentioning
confidence: 99%
“…), partially inhibits the fetal ACTH response to hypoxic hypoxia (Chang and Wood ), and almost completely inhibits the fetal ACTH response to brachiocephalic artery occlusion (a model of brain and carotid body ischemic hypoxia) (Powers and Wood ). Furthermore, we have demonstrated that intravenous injection of NMDA stimulates fetal ACTH secretion, and that the effect is partially dependent on prostaglandin biosynthesis (Knutson and Wood ). Boekkooi et al.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that ketamine, a clinically useful drug that blocks N-methyl-D-aspartate (NMDA) receptors (Mishra et al 2001), partially inhibits the fetal ACTH response to hypoxic hypoxia (Chang and Wood 2015), and almost completely inhibits the fetal ACTH response to brachiocephalic artery occlusion (a model of brain and carotid body ischemic hypoxia) (Powers and Wood 2007). Furthermore, we have demonstrated that intravenous injection of NMDA stimulates fetal ACTH secretion, and that the effect is partially dependent on prostaglandin biosynthesis (Knutson and Wood 2010). Boekkooi et al (1995) reported that ketamine interrupts the chemoreflex control of the heart rate in the late-gestation fetal sheep.…”
Section: Introductionmentioning
confidence: 99%